2018
DOI: 10.1155/2018/2734581
|View full text |Cite
|
Sign up to set email alerts
|

Bushenhuoxue Formula Facilitates Articular Cartilage Repair and Attenuates Matrix Degradation by Activation of TGF‐β Signaling Pathway

Abstract: Objective To investigate the effect and underlying mechanism of Bushenhuoxue (BSHX) formula on articular cartilage repair. Methods Twenty-four full-thickness cartilage defect rats were divided into two groups: model group and BSHX group (treated with BSHX formula). Macroscopic observation and histopathological study were conducted after 4- and 8-week treatment. Additionally, we also evaluated chondrocyte proliferation, extracellular matrix (ECM) deposition, cartilage degradation, and chondrocyte hypertrophy-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It has been established that the COcontaining formulae and MR have similar biological effects, including anti-inflammatory (Yu and Wang, 2018;Yu et al, 2021), anti-oxidative stress (Xu et al, 2006), and anti-apoptotic properties, to mitigate degenerative diseases (Pi et al, 2017;Yu et al, 2021). In a previous study, we found that MR could effectively attenuate cartilage degeneration and arthritic development (Yu et al, 2021), comparable to the therapeutic effect of CO-composed TCM formulas (Zhang et al, 2017b;Wang et al, 2018a;Dong et al, 2018;Yang et al, 2019;. Furthermore, we recently demonstrated that the classic TCM formula Liuwei Dihuang Decoction (a COcontaining formula) could effectively impede IVDD progression by reversing the high expression of p53 protein in NP cells (Zhang et al, 2021c).…”
Section: Introductionmentioning
confidence: 73%
“…It has been established that the COcontaining formulae and MR have similar biological effects, including anti-inflammatory (Yu and Wang, 2018;Yu et al, 2021), anti-oxidative stress (Xu et al, 2006), and anti-apoptotic properties, to mitigate degenerative diseases (Pi et al, 2017;Yu et al, 2021). In a previous study, we found that MR could effectively attenuate cartilage degeneration and arthritic development (Yu et al, 2021), comparable to the therapeutic effect of CO-composed TCM formulas (Zhang et al, 2017b;Wang et al, 2018a;Dong et al, 2018;Yang et al, 2019;. Furthermore, we recently demonstrated that the classic TCM formula Liuwei Dihuang Decoction (a COcontaining formula) could effectively impede IVDD progression by reversing the high expression of p53 protein in NP cells (Zhang et al, 2021c).…”
Section: Introductionmentioning
confidence: 73%
“…34,39 The expression of TGF-β1 could promote extracellular matrix deposition and improve local cartilage regeneration. 44 Although this study did not find an advantage of chondrocytes compared to MSCs for OA treatment, the findings expand the cell-based therapies for OA. The safety of genetically modified cells that particularly concerning in the treatment of other diseases, such as stroke, 45 was demonstrated in the closed joint cavity microenvironment.…”
Section: Discussionmentioning
confidence: 52%
“…The TGF-β superfamily signaling pathway is important in the development of the growth plate and the formation of permanent articular cartilage. Previous studies have indicated that TGF-β plays an important regulatory role in the maintenance of the normal cartilage cell phenotype, as well as in the promotion of proliferating cells to differentiate into mature cartilage cells ( 52-54 ). Similarly, the TGF-β signaling pathway helps to maintain the cartilage cell phenotype and the stability of the cartilage tissue environment ( 55 ).…”
Section: Discussionmentioning
confidence: 99%